Microsatellite instability in women with endometrial cancer from the Lodz region of Poland - Sobczuk, Anna; Smolarz, Beata; Romanowicz-Makowska, Hanna; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2008)
Objective: Microsatellite instability (MSI) seems to be important for the development of various human cancers including sporadic endometrial cancer. Material and methods: The aim of this study was to evaluate microsatellite instability in 100 postmenopausal women with endometrial cancer in DNA samples obtained from cancer tissue and blood of the same patients. Blood samples from age-matched healthy women served as controls (n=100). MSI was studied at five loci containing single- or dinucleotide repeat sequences and mapping to different chromosomal locations: BAT-25 (at locus 4q12), BAT-26 (2p16), D2S123 (2p16-p21), D5S346 (5q21-q22) and D17S250 (17q11.2-q12). Results: No differences in the MSI frequencies between blood and cancer tissue obtained from patients were detected. The microsatellite instability status was significantly higher in endometrial cancer tissue [40/100 (40%)] compared to controls [12/100 (12%)] (p<0.05). Conclusion: The results suggest that microsatellite instability seems to be important in the development of sporadic endometrial cancer.